2020
DOI: 10.3389/fgene.2020.00050
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in Fbxo11 Leads to Altered Immune Cell Content in Jeff Mouse Model of Otitis Media

Abstract: The Jeff mouse mutant carries a mutation in the F-box only 11 gene (Fbxo11) and heterozygous animals display conductive deafness due to the development of otitis media (OM). The Fbxo11 locus is also associated with chronic otitis media with effusion (COME) and recurrent OM in humans. The Jeff mutation affects the ability of FBXO11 to stabilize p53 that leads to perturbation in the TGF-beta/Smad2 signaling pathway important in immunity and inflammation. In the current study, we evaluated the effect of the Jeff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In the current study we found no statistical differences in the leukograms and only minimal changes for spleen WBC differentials for Fbxo11 Jf/+ and Mecom Jbo/+ mice compared to their respective wild-type littermates. In contrast, other studies report elevated blood neutrophils in Fbxo11 Jf/+ at P43-P44 (but not at P121-P127) ( Hardisty et al, 2003 ) and elevated blood neutrophil, macrophage, DC CD811 type, and NK cell differentials at 8 weeks ( Vikhe et al, 2020 ). The margin of neutrophil increase ( Fbxo11 Jf/+ 19.3% versus 16.6% wild-type littermates) in the latter study was smaller than the difference between males and females in inbred mouse strains ( Peters et al, 2002 ) and the percentage of neutrophils in Fbxo11 Jf/+ bulla fluid (10.3%) is actually lower than blood.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In the current study we found no statistical differences in the leukograms and only minimal changes for spleen WBC differentials for Fbxo11 Jf/+ and Mecom Jbo/+ mice compared to their respective wild-type littermates. In contrast, other studies report elevated blood neutrophils in Fbxo11 Jf/+ at P43-P44 (but not at P121-P127) ( Hardisty et al, 2003 ) and elevated blood neutrophil, macrophage, DC CD811 type, and NK cell differentials at 8 weeks ( Vikhe et al, 2020 ). The margin of neutrophil increase ( Fbxo11 Jf/+ 19.3% versus 16.6% wild-type littermates) in the latter study was smaller than the difference between males and females in inbred mouse strains ( Peters et al, 2002 ) and the percentage of neutrophils in Fbxo11 Jf/+ bulla fluid (10.3%) is actually lower than blood.…”
Section: Discussionmentioning
confidence: 80%
“…The margin of neutrophil increase ( Fbxo11 Jf/+ 19.3% versus 16.6% wild-type littermates) in the latter study was smaller than the difference between males and females in inbred mouse strains ( Peters et al, 2002 ) and the percentage of neutrophils in Fbxo11 Jf/+ bulla fluid (10.3%) is actually lower than blood. Other elevated blood myeloid classes represent small WBC populations; macrophages (<0.6%) and DC CD811 type (<3.3%) ( Vikhe et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…28,29 It is a regulator of the TGF-β pathway, the Jeff mutation maps to the Fbxo11 gene, and affects FBXO11 ability to stabilize p53 leading to perturbation in the TGF-β/Smad2 signaling pathway important in immunity and inflammation. 30,31 FBXO11 has been revealed to serve as an oncogene in many types of cancers. [32][33][34] Besides, Mei et al suggested that FBXO11 was involved in CSE-induced apoptosis, inflammation and airway remodeling by NNT-AS1/miR-582-5p/FBXO11 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…FBXO11 promotes the degradation of proteins critical in regulation of the cell cycle, such as BCL6, SNAIL and p53. Therefore, by acting as a sponge for miR-197-3p, circ-RBMS1 positively regulates FBXO11 expression in bronchial epithelial cells, enhancing CSE-induced apoptosis, inflammation, and oxidative stress [ 109 , 110 ].…”
Section: Circular Rnasmentioning
confidence: 99%